Performance study of orthogonal frequency division multiplexing (OFDM) in multipath environment [compact disc] - 455117 Maslinda Rasli (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunikasi)) - Universiti Teknologi Malaysia, 2005